Variation in the population structure of bluegill bully ( Gobiomorphus hubbsi ) with distance upriver: implications for river connectivity - Cindy F. Baker; Shad Mahlum; David K. Rowe (New Zealand Journal of Marine and Freshwater Research, 2025)
The bluegill bully is a small (TL